PELATIHAN PEMANFAATAN SAMPAH DAPUR MENJADI ANEKA MENU MAKANAN YANG LAYAK KONSUMSI, LEZAT, DAN SEHAT BAGI ANGGOTA PKK RW 02 KELURAHAN DINOYO KECAMATAN LOWOKWARU KOTA MALANG - Wahyuni, Nanik; Kartika, Ulfi; Suprayitno, Eko (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
Kitchen waste is rubbish that is produced from leftover food that cannot be processed, such as vegetables, skin of onions that unwittingly every day will be wasted and accumulate so much kitchen waste. If there are around 1500 households in Dinoyo, then the amount of garbage collected per day ranges from 4,500 kg to 7,500 kg. In order to reduce a lot of kitchen waste, the service aims to provide training on the use of kitchen waste into a variety of food menus that are suitable for consumption, delicious, and healthy for PKK RW 02 Dinoyo Urban District Lowokwaru District Malang City. The steps in implementing the training are the data collection stage and the training implementation stage. The target of the training participants are PKK RW 02 Dinoyo Subdistrict, Lowokwaru District, Malang City by providing direct practice in making various foods made from kitchen waste such as onion chips. The results of the training activities can increase the knowledge and skills of PKK mothers so that they can be practiced independently at home because the manufacturing process is quite easy and future prospects can help improve the community's economy.